A highly efficient and faithful MDS patient-derived xenotransplantation model for pre-clinical studies - Song, Yuanbin; Rongvaux, Anthony; Taylor, Ashley; Jiang, Tingting; Tebaldi, Toma; Balasubramanian, Kunthavai; Bagale, Arun; Terzi, Yunus Kasim; Gbyli, Rana; Wang, Xiaman; Fu, Xiaoying; Gao, Yimeng; et al. (Nature communications, 2019)
Comprehensive preclinical studies of Myelodysplastic Syndromes (MDS) have been elusive due to limited ability of MDS stem cells to engraft current immunodeficient murine hosts. Here we report a MDS patient-derived xenotransplantation model in cytokine-humanized immunodeficient “MISTRG” mice that provides efficient and faithful disease representation across all MDS subtypes. MISTRG MDS patient-derived xenografts (PDX) reproduce patients’ dysplastic morphology with multi-lineage representation, including erythro- and megakaryopoiesis. MISTRG MDS-PDX replicate the original sample’s genetic complexity and can be propagated via serial transplantation. MISTRG MDS-PDX demonstrate the cytotoxic and differentiation potential of targeted therapeutics providing superior readouts of drug mechanism of action and therapeutic efficacy. Physiologic humanization of the hematopoietic stem cell niche proves critical to MDS stem cell propagation and function in vivo. The MISTRG MDS-PDX model opens novel avenues of research and long-awaited opportunities in MDS research. Myelodyplastic hematopoietic stem cells (MDS HSC) have eluded in vivo modeling. Here the authors present a highly efficient MDS patient-derived xenotransplantation model in cytokine-humanized mice with replication of the donors’ genetic complexity and myeloid, erythroid, and megakaryocytic lineage dysplasia.